2012
DOI: 10.1590/s0037-86822012000200027
|View full text |Cite
|
Sign up to set email alerts
|

Bruns' syndrome and racemose neurocysticercosis: a case report

Abstract: Cysticercosis is an infection caused by the larval stage of the tapeworm Taenia solium. The parasite may infect the central nervous system, causing neurocysticercosis (NCC). The clinical manifestations depend on load, type, size, location, stage of development of the cysticerci, and the host's immune response against the parasite. The racemose variety occurs in the ventricles or basal cisterns and is a malignant form. Mobile ventricular mass can produce episodic hydrocephalus on changing head posture with atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…The MRI is superior to tomography for the diagnosis of neurocysticercosis. 6 When the ventricular form is accompanied by meningitis and hydrocephalus, mortality is greater than 50%, and most patients die within 2 years, even with the VPS. The prognosis of the intraventricular form is worse than that of the intraparenchymal form, and it follows a progressive course, due to obstructive hydrocephalus, intracranial hypertension and meningeal infection.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI is superior to tomography for the diagnosis of neurocysticercosis. 6 When the ventricular form is accompanied by meningitis and hydrocephalus, mortality is greater than 50%, and most patients die within 2 years, even with the VPS. The prognosis of the intraventricular form is worse than that of the intraparenchymal form, and it follows a progressive course, due to obstructive hydrocephalus, intracranial hypertension and meningeal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe the cases of two patients who developed Bruns syndrome secondary to fourth ventricular neurocysticercosis and review 12 similar cases reported in the English literature [5][6][7][8][9] (Table 1). Cases were identified in the literature by a PubMed search using terms "intraventricular neurocysticercosis" and "Bruns."…”
Section: -9mentioning
confidence: 99%
“…During the course of the disease, the patient had critical days with acute headache, dizziness, complete abnormal gait due to ataxia and lateralization with compromised state of consciousness, manifestations explained by Bruns syndrome (13)(14)(15).…”
Section: Case Presentationmentioning
confidence: 99%